Use of hormonal contraception and attempted suicide: a nested case-control study. (1st June 2022) - Toffol, E.; Partonen, T.; Latvala, A.; But, A.; Heikinheimo, O.; Haukka, J.
Abstract : Introduction: In Finland more than 40% of fertile aged women used some type of hormonal contraception (HC) in the period 2010-2013. A proportion of women using HC complains of side effects, including mood symptoms. The relationship between the use of HC and the risk of attempted suicide (AS) is still a matter of debate. Objectives: To assess the association of the use of HC with the risk of AS during 2017-2019. Methods: Data were retrieved from the Prescription Centre, Care Register of Health Care, Register of Primary Health Care Visits and Statistics Finland. A total of 587 823 women, aged 15-49 years, using and not using HC in 2017 were analysed in the initial incidence study. All incident AS cases during 2018-2019, and their 4:1 age-matched controls (1 174 346 person-years) were analysed in a nested case-control setting via conditional logistic regression models. Results: Altogether 818 AS cases occurred during the follow-up (incidence rate: 0.70/1000 person-years, 95% CI 0.65–0.75), with an IRR of HC vs. no-HC use of 0.73 (0.63–0.83). Current use (in the 180 days before the event) of estradiol- or ethinylestradiol-containing HC was associated with a lower risk of AS (0.53, 0.33–0.87; 0.49, 0.37–0.64, respectively) compared to non-use of HC. After controlling for covariates (marital and socioeconomic status, education level, use of psychotropic medications), only current use of HC containing ethinylestradiol remained significant (0.39, 0.23–0.65). Conclusions: A lower risk of AS is associated with the use of HC, and specifically of ethinylestradiol-containing HC. Disclosure: No significant relationships.